The effect of the transition command on the long jump performance by visually impaired athletes - Silva, Carlos Antonio (2020)
This study investigated the effects of transition command related to caller location (front, back, right and left side of the take-off board) and type of caller communication (voice and clap hands) on the long jump performance by visually impaired athletes. Eight long jumpers with visual impairment (T11 class), both male and female, with an average age of 26.35 years (± 6.29), and their respective callers (n = 5) took part in this experiment. Two conditions were experimentally manipulated: (i) caller location and (ii) type of communication. Two long jumps were performed in each location under each type of communication, totalizing 16 long jumps per athlete. Results showed that type of command, as well as the callers' locations, affected similarly the performance of the long jump by visually impaired athletes. They also showed that athletes and callers' preferences for the type of transition command and positioning location had the same effects.